2D/3D Hybrid Cs2AgBiBr6 Double Perovskite Solar Cells: Improved Energy Level Alignment for Higher Contact‐Selectivity and Large Open Circuit Voltage. Issue 7 (9th January 2022) - Sirtl, Maximilian T.; Hooijer, Rik; Armer, Melina; Ebadi, Firouzeh G.; Mohammadi, Mahdi; Maheu, Clément; Weis, Andreas; van Gorkom, Bas T.; Häringer, Sebastian; Janssen, René A. J.; Mayer, Thomas; Dyakonov, Vladimir; et al.
Abstract: Since their introduction in 2017, the efficiency of lead‐free halide perovskite solar cells based on Cs2 AgBiBr6 has not exceeded 3%. The limiting bottlenecks are attributed to a low electron diffusion length, self‐trapping events and poor selectivity of the contacts, leading to large non‐radiative V OC losses. Here, 2D/3D hybrid double perovskites are introduced for the first time, using phenethyl ammonium as the constituting cation. The resulting solar cells show an increased efficiency of up to 2.5% for the champion cells and 2.03% on average, marking an improvement by 10% compared to the 3D reference on mesoporous TiO2 . The effect is mainly due to a V OC improvement by up to 70 mV on average, yielding a maximum V OC of 1.18 V using different concentrations of phenethylammonium bromide. While these are among the highest reported V OC values for Cs2 AgBiBr6 solar cells, the effect is attributed to a change in recombination behavior within the full device and a better selectivity at the interface toward the hole transporting material (HTM). This explanation is supported by voltage‐dependent external quantum efficiency, as well as photoelectron spectroscopy, revealing a better energy level alignment and thus a better hole‐extraction and improved electron blocking at the HTM interface. Abstract : Solar cells comprised of a lead‐free Cs2 AgBiBr6 ‐based 2D/3D hybrid double perovskite with PEA + as constituting cation show an increase of the power conversion efficiency by almost 10% due to a large increase in the V OC . This is attributed to a better contact selectivity caused by an improved energy level alignment at the interface between the perovskite layer and the hole‐transporting material.